Alessandro Taddei, Hagia Sophia before Hagia Sophia. A study of the Great Church of Constantinople from its origins to the Nika Revolt of 532 - ΧΑΤΖΗΛΑΖΑΡΟΥ (Dimitris Th. CHATZILAZAROU), Δημήτρης Θ. (Δελτίον της Χριστιανικής Αρχαιολογικής Εταιρείας, 2021)
Alessandro Taddei, Hagia Sophia before Hagia Sophia. A study of the Great Church of Constantinople from its origins to the Nika Revolt of 532 (Saggi di storia dell’arte, 52), Campisano Editore, Ρώμη 2017, 310 σελ., 157 εικ., 15,50×21,50 εκ. ISBN: 978-88-85795-00-6.